PELAKSANAAN RESES ANGGOTA DPRD KOTA PEKANBARU DAPIL V TAMPAN TAHUN 2019 - Wati, Nurhafiza; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Recess is a period in which DPRD members carry out activities outside the session period, especially outside the DPRD building, whether carried out individually or in groups by DPRD members to carry out regular working visits to their electoral districts to absorb and gather constituent aspirations in order to realize a sense of justice and welfare. in the fields of development, governance, social and economic matters relating to people's lives. The organizers of the recess are the leaders and members of the Pekanbaru City DPRD as many as 45 people, facilitated by the Pekanbaru City DPRD secretariat. Dapil V (five) is an electoral district which includes the Umbrella Sekaki sub-district and the handsome sub-district and is one of the areas where the recess activities are carried out.The purpose of this study is to find out how the recess of members of the Pekanbaru City DPRD in the handsome Dapil V in 2019 is carried out and what are the factors supporting the implementation of the recess for members of the Pekanbaru City DPRD in the Handsome Dapil V in 2019. This study uses a qualitative approach with descriptive methods. In collecting data, the author uses interview and documentation techniques.The results of this study are that the implementation of the recess carried out by members of the Pekanbaru City DPRD in the Handsome Dapil V in 2019 can be categorized as effective, because it has carried out the recess according to the set time and has made a report based on the aspirations absorbed in the V (five) electoral districts and has realized community aspirations conveyed during the recess. On the other hand, the supporting factors for the implementation of the recess for the Pekanbaru City DPRD members in the V (five) regions are the cost of implementing the recess, community participation, and facilities and infrastructure. Keywords: Mandate of People's Representatives, Legislation of Recess, Accommodating Aspiration.